Effect of the addition of essential oils, enzymes, ionophores and combinations of feed additives in finishing cattle diets - Meschiatti, Murillo Alves Porto (2019)
Regardless of the type of diet used, the search for increased digestion of nutrients has been the target of most research worldwide. The objective of this thesis was to evaluate the effects of the inclusion of essential oils, enzymes, ionophores and combinations of additives in animal performance, ruminal health and apparent digestibility in Nellore cattle fed with high concentrate diets. The study was composed of two performance experiments and two of metabolism In Chapter 1 of this thesis 2 experiments were conducted to evaluate the performance responses of finishing feedlot cattle receiving diets containing essential oils and exogenous enzymes. The treatments in each experiment consisted of (dry matter basis): MON - sodium monensin (26 mg/kg); BEO - a blend of essential oils (90 mg/kg); BEO+MON - a blend of essential oils plus monensin (90 mg/kg + 26 mg/kg, respectively); BEO+AM - a blend of essential oils plus exogenous α-amylase (90 mg/kg + 560 mg/kg, respectively); and BEO+AM+PRO - a blend of essential oils plus exogenous α-amylase and exogenous protease (90 mg/kg + 560 mg/kg + 840, mg/kg respectively). Exp. 1 consisted of a 93-d finishing period using 300 Nellore bulls in a randomized complete block design. Compared with MON, the combination of BEO+AM resulted in greater dry matter intake, greater average daily gain, 12 kg heavier hot carcass weight, although feed efficiency was not significantly different between BEO+AM and MON. BEO+MON and BEO did not improve performance when compared to MON. In Exp. 2, five ruminally cannulated Nellore steers were used to evaluate intake, apparent total tract digestibility of nutrients, and ruminal parameters in a 5 × 5 Latin Square design. Intakes of all nutrients measured, except for EE were greater in animals fed BEO+AM when compared with MON, with no differences on total tract nutrient digestibilities between these two treatments. Feeding BEO increased the total tract digestibility of CP compared to MON. In summary, diets containing the BEO used herein enhanced dry matter intake of growing-finishing feedlot cattle compared with a basal diet containing MON without impair feed efficiency. A synergism between BEO and AM was detected, resulting in increased carcass production. This study evaluated the growth performance and digestion responses of finishing feedlot beef cattle fed high-concentrate diets containing 82.5% flint corn (DM basis) ground to medium (1.66 mm; MG) or coarse particle sizes (2.12 mm; CG), added with monensin (26 mg/kg; DM basis; MON) or a blend of essential oils + exogenous α-amylase (90 mg/kg + 560 mg/kg commercial product, respectively, DM basis; BEO+AM). In Exp. 1, 256 Nellore bulls were blocked by initial body weight (360 ± 12 kg), assigned to 48 pens and pens within blocks were randomly assigned, in a 2 × 2 factorial arrangement, to treatments during 99 d. Feed additive effect was detected for DMI, which was greater for bulls fed BEO+AM vs. MON. The HCW was 11 kg heavier for bulls fed BEO+AM vs. MON in diets containing CG, but not MG particle size. In Exp. 2, four ruminally cannulated Nellore steers were offered the same treatments of Exp. 1, in a 4 × 4 Latin Square design, to evaluate intake, apparent total tract digestibility of diets and ruminal fermentation parameters. Effect of corn particle size was detected for intake of DM, CP, NDF, NFC, starch and TDN which were greater for steers fed CG than steers fed MG corn. Feed additive affected (P = 0.02) ruminal NH3-N concentration, which was less for steers fed BEO+AM compared to MON. In summary, reducing flint corn particle size from 2.12 to 1.66 mm in finishing diets failed to improve cattle growth performance, digestibility of most nutrients and ruminal fermentation characteristics. A blend of essential oils associated with exogenous α-amylase resulted in the heavier carcass weights compared to monensin supplementation when included in diets containing coarse ground corn.